2018
DOI: 10.1242/jeb.182121
|View full text |Cite
|
Sign up to set email alerts
|

Cooler snakes respond more strongly to infrared stimuli, but we have no idea why

Abstract: The pit organ defining pit vipers (Crotalinae) contains a membrane covered with temperature receptors that detect thermal radiation from environmental surfaces. Temperature is both the environmental parameter being sensed and the mechanism by which the pit membrane detects the signal. As snakes are ectotherms, temperature also has a strong influence on neurological and locomotor responses to the signal. This study of Pacific rattlesnakes () systematically examined the effect of body, target and background temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Similarly, a higher metabolic rate induced by increased temperatures can cause a higher feeding rate in response to hunger level (Frances & McCauley, 2018; Walker et al, 2020). Finally, the functioning of sensory receptors can also be temperature‐dependent, and therefore modify the quality of the information acquired from the environment and the following behavioral response, even if the underlying cognitive processes remain unchanged (Bakken et al, 2018). 2 Separating these mechanistic effects of temperature on perception from cognitive effects is likely to require controlled laboratory studies to complement field results.…”
Section: The State Of Knowledgementioning
confidence: 99%
“…Similarly, a higher metabolic rate induced by increased temperatures can cause a higher feeding rate in response to hunger level (Frances & McCauley, 2018; Walker et al, 2020). Finally, the functioning of sensory receptors can also be temperature‐dependent, and therefore modify the quality of the information acquired from the environment and the following behavioral response, even if the underlying cognitive processes remain unchanged (Bakken et al, 2018). 2 Separating these mechanistic effects of temperature on perception from cognitive effects is likely to require controlled laboratory studies to complement field results.…”
Section: The State Of Knowledgementioning
confidence: 99%
“…Taken together, these observations suggest that evolutionary reductions in thermosensing ion channels may be a specialization for somatosensory organs that must operate well below core body temperatures. Curiously, an enhanced sensory response has been observed in the rattlesnake pit organ when cold, as it responds more strongly to stimuli at cooler temperatures than at warm temperatures (Bakken et al, 2018; Cadena et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2) 25 . Also, laboratory studies have reported robust behavioural responses 14,15,26 and higher strike success 15 when thermal contrast between target and background was large and positive (target warmer than background). This preference for positive thermal contrast might be related to observations of antiphase tracking of moving pendulum targets with negative contrast 14,27 , which should be inimical to strike success.…”
Section: Discussionmentioning
confidence: 99%
“…The models included a random intercept for snake ID to statistically account for the non-independence of repeated measurements from the same snake. Snakes respond to positive and negative thermal contrast, though response to negative contrast is typically weaker 14,15,26 . We therefore analysed absolute contrast values.…”
Section: Methodsmentioning
confidence: 99%